2014
DOI: 10.1128/iai.01224-13
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Protein P5 Is Required for Resistance of Nontypeable Haemophilus influenzae to Both the Classical and Alternative Complement Pathways

Abstract: The complement system is an important first line of defense against the human pathogen Haemophilus influenzae. To survive and propagate in vivo, H. influenzae has evolved mechanisms for subverting this host defense, most of which have been shown to involve outer surface structures, including lipooligosaccharide glycans and outer surface proteins. Bacterial defense against complement acts at multiple steps in the pathway by mechanisms that are not fully understood. Here we identify outer membrane protein P5 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 76 publications
2
47
0
1
Order By: Relevance
“…In contrast to Rd, which originally was an encapsulated serotype d strain that lost the capsule, various NTHi strains are constantly under selective pressure for the acquisition of virulence factors that can contribute to serum resistance. Recent studies have shown that NTHi are able to evade IgM binding [31,32] and to scavenge complement inhibitors, C4BP and Factor H [33,34]. The NTHi 375 strain may potentially employ some mechanisms of immune evasion facilitating the observed serum resistance.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to Rd, which originally was an encapsulated serotype d strain that lost the capsule, various NTHi strains are constantly under selective pressure for the acquisition of virulence factors that can contribute to serum resistance. Recent studies have shown that NTHi are able to evade IgM binding [31,32] and to scavenge complement inhibitors, C4BP and Factor H [33,34]. The NTHi 375 strain may potentially employ some mechanisms of immune evasion facilitating the observed serum resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Decrease cell surface binding of the complement activator IgM [2] Vitronectin Inhibition of complement [12] …”
Section: Organism Molecule(s) Mechanism Of Evasion Referencementioning
confidence: 99%
“…uses CspA for binding of host-derived proteins and/or direct interaction with the formation of the terminal complement complex, as a mechanism for evasion [5] and [6]. These and other examples, including mechanisms used by N. meningitidis, are shown in Table 1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that the interaction between NTHi (strain NT127), but not the interaction between the encapsulated strain RdKW20, and FH is mediated by P5, a protein previously known to be involved in bacterial attachment to mucosal surfaces (51,52). This difference between NTHi and H. influenzae type d (RdKW20) is likely due to the sequence variations in P5, and may also account for the lack of affinity for FH observed with the Hib and Hif PH mutants (53,54).…”
Section: Discussionmentioning
confidence: 99%